Nanoscience and Technology 2009
DOI: 10.1142/9789814287005_0027
|View full text |Cite
|
Sign up to set email alerts
|

The potential and challenges of nanopore sequencing

Abstract: A nanopore-based device provides single-molecule detection and analytical capabilities that are achieved by electrophoretically driving molecules in solution through a nano-scale pore. The nanopore provides a highly confined space within which single nucleic acid polymers can be analyzed at high throughput by one of a variety of means, and the perfect processivity that can be enforced in a narrow pore ensures that the native order of the nucleobases in a polynucleotide is reflected in the sequence of signals t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
710
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 506 publications
(721 citation statements)
references
References 11 publications
7
710
0
4
Order By: Relevance
“…In nanopore analytics, single molecules are detected via the passage-induced changes in ionic current. [2][3][4][5][6][7] The approach can be implemented with protein 4,[8][9][10] and solid-state nanopores [10][11][12][13][14][15][16] and has gained popularity 17 due to its simplicity, the wide range of accessible analytes, 2,13,[18][19][20] and the prospect of DNA sequencing [21][22][23] based on nucleic acid sensing. [24][25][26][27] The translocation of protein and DNA strands through protein channels is also a biologically relevant process in pathogenic bacteria and human cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In nanopore analytics, single molecules are detected via the passage-induced changes in ionic current. [2][3][4][5][6][7] The approach can be implemented with protein 4,[8][9][10] and solid-state nanopores [10][11][12][13][14][15][16] and has gained popularity 17 due to its simplicity, the wide range of accessible analytes, 2,13,[18][19][20] and the prospect of DNA sequencing [21][22][23] based on nucleic acid sensing. [24][25][26][27] The translocation of protein and DNA strands through protein channels is also a biologically relevant process in pathogenic bacteria and human cells.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed insight has been gained from studies on pores of known molecular structure and the electrophoretically-driven movement of individual DNA and RNA strands. 3,11,21,23,[28][29][30] Several biophysical parameters have been determined such as threading frequency, [31][32][33][34] orientation of strands, [35][36][37][38][39] velocity of DNA transport, 40 influence of pore geometry, 41 and interactions with the pore wall. 39 In addition to nucleic acids, translocation has also been investigated for peptides, [42][43][44][45] proteins, [46][47][48] and peptide-oligonucleotide conjugates, 49 which, unlike nucleic acid strands, frequently feature inhomogeneous charge distributions and vary considerably in diameter along the polymer sequence.…”
Section: Introductionmentioning
confidence: 99%
“…1 This discovery initiated a surge of proposals for novel DNA sequencing protocols. 2,3 Among the many, Zwolak et al proposed to sort the nucleobases from each other in a sequence by measuring the transverse tunneling current across a ssDNA as this is driven through a nanopore. 4 It was suggested that single base resolution is, in principle, achievable, as the differences in the electronic structure among the nucleobases may translate into distinguishable tunneling current signals.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22][23][24] Moreover, the signal, which is based on the native order of the nucleobases in a polynucleotide, can facilitate rapid sequencing of DNA or RNA. [25][26][27][28][29][30][31] One attractive approach to synthetically mimic nature is "molecular imprinting," which is used in the preparation of substrate-selective recognition sites within a matrix using a molecular template. Polyakov 32 reported effects from the presence of organic solvents, such as benzene, toluene, and xylene, on a silica pore structure, and Pauling 33,34 and Dickey 35 later reported on silica gel polymerization using sodium silicate to selectively absorb various organic dyes.…”
Section: Introductionmentioning
confidence: 99%